Collective intelligence for monitoring innovation and change in manufacturing industry - (:unkn) unknown (Newswood Limited, 2012)
Change monitoring and management become an unavoidable necessity for companies in order to stay competitive in global market.This requires thorough handling models for change management to attain a systematic approach. In this paper, monitoring models for innovation and changes in manufacturing environments are investigated using two collective intelligence approaches. The first approach is based on a multi agent system designed in a tree-structured, where expert operational agents are strictly organised under sub-chair agents. The second approach uses a swarm intelligence approach, namely bee-colony algorithm to achieve collective intelligence for monitoring innovation and change across the manufacturing companies. © 2012 Newswood Limited. All rights reserved.
Keywords: Change Management; Collective Intelligence; Innovation Monitoring; Multi Agent Aystems; Swarm Intelligence